2017
DOI: 10.1016/j.sjpain.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cytokines for treatment of neuropathic pain

Abstract: AbstractBackgroundNeuropathic pain is a challenging condition often refractory to existing therapies. An increasing number of studies have indicated that the immune system plays a crucial role in the mediation of neuropathic pain. Exploration of the various functions of individual cytokines in neuropathic pain will provide greater insight into the mechanisms of neuropathic pain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
133
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 119 publications
1
133
0
2
Order By: Relevance
“…Many studies have demonstrated that pain behaviors can be attenuated by local or spinal administration of agents that antagonize TNF-α (105)(106)(107)(108). TNF soluble receptor (TNFSR), commercially known as etanercept, is previously approved by the FDA for treatment of painful inflammatory conditions including rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis (109). While preclinical trials with recombinant TNFSR have shown promise, randomized clinical trials have had limited success (109).…”
Section: Tumor Necrosis Factor and Pathological Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that pain behaviors can be attenuated by local or spinal administration of agents that antagonize TNF-α (105)(106)(107)(108). TNF soluble receptor (TNFSR), commercially known as etanercept, is previously approved by the FDA for treatment of painful inflammatory conditions including rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis (109). While preclinical trials with recombinant TNFSR have shown promise, randomized clinical trials have had limited success (109).…”
Section: Tumor Necrosis Factor and Pathological Painmentioning
confidence: 99%
“…TNF soluble receptor (TNFSR), commercially known as etanercept, is previously approved by the FDA for treatment of painful inflammatory conditions including rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis (109). While preclinical trials with recombinant TNFSR have shown promise, randomized clinical trials have had limited success (109). Clinical translation may be limited by the potential loss of beneficial neuroprotective and neuroregenerative properties of TNF-α, and by its impermeability at the blood-brain-barrier (9).…”
Section: Tumor Necrosis Factor and Pathological Painmentioning
confidence: 99%
“…interleukin‐1 β (IL‐1 β ), IL‐18, IL‐6 and nitric oxide synthase 2 (NOS2)] and antinociceptive factors [e.g. IL‐1 receptor antagonist (IL‐1RA), IL‐18 binding protein (IL‐18BP) and IL‐10] contributes to the development of neuropathic pain . Moreover, research on chemokines has suggested that their systems (ligands/receptors) are involved in pathological nociceptive processes .…”
Section: Introductionmentioning
confidence: 99%
“…IL-1 receptor antagonist (IL-1RA), IL-18 binding protein (IL-18BP) and IL-10] contributes to the development of neuropathic pain. [6][7][8][9] Moreover, research on chemokines has suggested that their systems (ligands/receptors) are involved in pathological nociceptive processes. [10][11][12] Our recent results indicated that the blockade of some chemokine receptors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that lncRNA Musmusculus predicted gene 14,461 (Gm14461) was highly expressed in injured DRG 6 days after spinal nerve ligation in mice with neuropathic pain, suggesting that Gm14461 may be involved in regulating neuropathic pain [11]. Diverse causes of neuropathic pain are associated with excessive inflammation [12,13]. Cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 play a very important role in the pathogenesis of TN by regulating the immune response within the peripheral endings of trigeminal ganglion neurons (TGNs) [14].…”
Section: Introductionmentioning
confidence: 99%